Incorporating Technology in Education: An Evaluation of NEP 2020’s Vision for Digital Learning - Gururaja CS (AG Volumes, 2025)
"The National Education Policy 2020 (NEP 2020)" seeks to use digital efforts to transform education in India. The way ahead is digital education, which uses digital gadgets and technology to provide instruction. Everywhere in the nation, digital education improved the comfort of learners. The internet is having an impact on the whole planet, and the current era is driven by digital technology. Another name for digital education is an e-learning platform. In this study, review the various literature’s on NEP 2020’s vision for digital learning and explore the importance of digital technology in education. According to its findings, "the National Education Policy (NEP) 2020" represents a significant advancement in India’s educational digitalisation, with the goal of closing the digital divide and advancing fair access to high-quality education via technology. Recognising that competent teachers are crucial for successful technology integration in the classroom, the strategy places an emphasis on improving teacher training, building digital infrastructure, and creating high-quality digital material.